Task assignment and organizational form - Kerstin Puschke (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
This paper shows that a firm prefers a process-based task assignment compared to a function based one if the tasks are from functional areas which are neither too complementary nor too substitutable. We consider several projects with contributions from several functional areas. The organization can be structured along processes like product lines (M-form) or along functional areas like marketing or production (U-form). The U-form enables cost savings due to specialization or scale economies. We show that the more effective incentives under the M-form might outweigh these savings if the functions are neither too complementary nor too substitutable.
Keywords: D02; L23; 330; Task Assignment; Organizational Form; Incomplete Contracts